EVALUATION OF SEALING PROPERTIES OF THERMAFIL AND ULTRAFIL TECHNIQUES IN THE ABSENCE OR PRESENCE OF SMEAR LAYER - (:unkn) unknown (WILLIAMS & WILKINS, 1993)
The apical sealing abilities of two thermoplasticized gutta-percha techniques were evaluated. A total of 128 single-rooted teeth were divided into six groups in which Ultrafil, Thermafil, and lateral condensation techniques, with and without the smear layer, were used to obturate 20 roots in each group. The roots were implanted subcutaneously in rats for 90 days to expose the materials to vital tissue and tissue fluids. The roots were recovered, immersed in 1% methylene blue for 2 wk, cleared, and the dye penetration was measured using a dissecting microscope. Thermafil showed the least leakage with smear layer present and Ultrafil the least with it absent. The two thermoplasticized gutta-percha techniques both showed significantly less leakage than lateral condensation with and without the smear layer. Removing the smear layer reduced the leakage significantly in all groups.
Keywords: THERMOPLASTICIZED GUTTA-PERCHA; OBTURATION TECHNIQUES; APICAL SEAL; ABILITY; REMOVAL